Partnership dynamics and entry into parenthood: Comparison of Finnish birth cohorts 1969–2000 - Leen Rahnu Leen; Jalovaara Marika (Turun yliopisto, 2022)
During the past decade, the stability of close-to-replacement-level fertility ended in all Nordic countries, with the decline to the lowest level in Finland. Whether and how partnership dynamics have changed and whether they play a role in fertility developments is not clear. We focus on patterns of and associations between the formation and stability of co-residential partnerships and first birth, and whether and how they have changed across recent Finnish birth cohorts. We use total population register data on women and men born between 1969 and 2000 in Finland, and event history methods. The results indicate that half of the women formed their first co-residential partnership by the age of 22. Cohorts born in the early 1990s were the first to delay the formation of non-marital first partnerships. By contrast, first birth is increasingly postponed, and the proportion of women and men who ever become parents has declined across recent cohorts. Among men, we observe higher median ages for family formation events and a higher likelihood of not forming a family. As a result of the fertility decline and increase in partnership instability, the probability of separation among partnered women born in the 1990s is for the first time higher than the probability of first birth. Our findings show that at a behavioural level, the once close link between partnership formation and parenthood has progressively eroded across consecutive birth cohorts. Together with the ongoing tendency to delay first birth, decreasing partnership stability, and first indications of delaying partnership formation, the potential of witnessing a marked increase of fertility levels in the near future is delimited. The results contribute to a better understanding of the demographic mechanism behind the decline in fertility in Finland over the recent decade.